2023
DOI: 10.3389/fdgth.2023.1173229
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Japanese consumers' attitudes toward the digital transformation of OTC medicine purchase behavior and eHealth literacy: an online survey for digital experience design

Abstract: IntroductionSince the enactment of the revised Pharmaceutical Affairs Act in Japan in 2009, self-medication practices have increased in the country. However, studies report that consumers pay little attention to the medication facts and risks indicated on the packages of over-the-counter (OTC) medicines, which could be a potential risk. Since the COVID-19 pandemic, the digital transformation of purchasing OTC medicines has progressed. As an appropriate design for the digital transformation is likely to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The studies included in this review reveal that the availability of various drug products and more options ( Little et al, 2020 ; Cokro and Arfenda, 2023 ), wide-spread availability ( Tang et al, 2023 ), and 24-h availability ( Tang et al, 2023 ) were primary motivators for purchasing medication online. Unavailability in the local market ( Abanmy, 2017 ; Bowman et al, 2020 ) and drugs not for sale in a country ( Koenraadt and van de Ven, 2018 ) were also positively related to increased purchase behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included in this review reveal that the availability of various drug products and more options ( Little et al, 2020 ; Cokro and Arfenda, 2023 ), wide-spread availability ( Tang et al, 2023 ), and 24-h availability ( Tang et al, 2023 ) were primary motivators for purchasing medication online. Unavailability in the local market ( Abanmy, 2017 ; Bowman et al, 2020 ) and drugs not for sale in a country ( Koenraadt and van de Ven, 2018 ) were also positively related to increased purchase behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Convenience was also a dominant motivation for purchasing behavior. Consumers who bought medications online indicated that buying drugs online was more convenient ( Brijnath et al, 2015 ; Abanmy, 2017 ; Koenraadt and van de Ven, 2018 ; Little et al, 2020 ; Almomani et al, 2023 ; Anis and Tan, 2023 ; Tang et al, 2023 ) and saved time ( Almohammed et al, 2023 ; Almomani et al, 2023 ). Other convenience-related motivations included easy access ( Alwhaibi et al, 2021 ; Almomani et al, 2023 ), bypassing gatekeepers ( Almomani et al, 2023 ), home delivery ( Koenraadt and van de Ven, 2018 ), the importance of rapid retrieval of information ( Little et al, 2020 ), price comparison ( Little et al, 2020 ), and time efficiency ( Little et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of nearly 300 articles about the relationship between humans and information technologies during the COVID-19 pandemic found that information technologies were mainly used in specific domains like education and employment, and also used in healthcare and daily use ( Vargo et al, 2021 ). A few articles report how OAs have used these technologies for healthcare and family interactions ( Elbaz et al, 2021 ; Racin et al, 2023 ; Tang et al, 2023 ).…”
Section: Related Workmentioning
confidence: 99%
“…A meta-analysis of nearly 300 articles about the relationship between humans and information technologies during the COVID-19 pandemic found that information technologies were mainly used in specific domains like education and employment, and also used in healthcare and daily use (Vargo et al, 2021). A few articles report how OAs have used these technologies for healthcare and family interactions (Elbaz et al, 2021;Racin et al, 2023;Tang et al, 2023).…”
Section: Covid-19 and Societiesmentioning
confidence: 99%